Infiltration and sealing for managing non-cavitated proximal lesions: a systematic review and meta-analysis - Yuanyuan Chen; Dongru Chen; Huancai Lin (BMC, 2021)
Abstract Background Infiltration and sealing are micro-invasive treatments for arresting proximal non-cavitated caries lesions; however, their efficacies under different conditions remain unknown. This systematic review and meta-analysis aimed to evaluate the caries-arresting effectiveness of infiltration and sealing and to further analyse their efficacies across different dentition types and caries risk levels. Methods Six electronic databases were searched for published literature, and references were manually searched. Split-mouth randomised controlled trials (RCTs) to compare the effectiveness between infiltration/sealing and non-invasive treatments in proximal lesions were included. The primary outcome was obtained from radiographical readings. Results In total, 1033 citations were identified, and 17 RCTs (22 articles) were included. Infiltration and sealing reduced the odds of lesion progression (infiltration vs. non-invasive: OR = 0.21, 95% CI 0.15-0.30; sealing vs. placebo: OR = 0.27, 95% CI 0.18-0.42). For both the primary and permanent dentitions, infiltration and sealing were more effective than non-invasive treatments (primary dentition: OR = 0.30, 95% CI 0.20-0.45; permanent dentition: OR = 0.20, 95% CI 0.14-0.28). The overall effects of infiltration and sealing were significantly different from the control effects based on different caries risk levels (OR = 0.20, 95% CI 0.14-0.28). Except for caries risk at moderate levels (moderate risk: OR = 0.32, 95% CI 0.01-8.27), there were significant differences between micro-invasive and non-invasive treatments (low risk: OR = 0.24, 95% CI 0.08-0.72; low to moderate risk: OR = 0.38, 95% CI 0.18-0.81; moderate to high risk: OR = 0.17, 95% CI 0.10-0.29; and high risk: OR = 0.14, 95% CI 0.07-0.28). Except for caries risk at moderate levels (moderate risk: OR = 0.32, 95% CI 0.01-8.27), infiltration was superior (low risk: OR = 0.24, 95% CI 0.08-0.72; low to moderate risk: OR = 0.38, 95% CI 0.18-0.81; moderate to high risk: OR = 0.20, 95% CI 0.10-0.39; and high risk: OR = 0.14, 95% CI 0.05-0.37). Conclusion Infiltration and sealing were more efficacious than non-invasive treatments for halting non-cavitated proximal lesions.